2010
DOI: 10.1159/000320588
|View full text |Cite
|
Sign up to set email alerts
|

Generic and Disease-Specific Measures of Quality of Life in Patients with Mild Alzheimer’s Disease

Abstract: Background/Aim: The aim of the study was to investigate the pattern of association of generic and disease-specific quality of life (QoL) scales with standard clinical outcome variables in Alzheimer’s disease (AD). Methods: The participants were 321 home-living patients with mild AD and their primary caregivers from the Danish Alzheimer Intervention Study. QoL was assessed using the generic EuroQol-5D with visual analogue scale (VAS) and the disease-specific Quality of Life in Alzheimer’s Disease (QOL-AD) scale… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

2
28
0
1

Year Published

2011
2011
2023
2023

Publication Types

Select...
9

Relationship

1
8

Authors

Journals

citations
Cited by 30 publications
(31 citation statements)
references
References 56 publications
2
28
0
1
Order By: Relevance
“…The association between increased depressive symptoms and reduced QOL is well established in LOD, as most studies show this to be a significant factor across dementia severity and type of residency [28-35]. Neuropsychiatric symptoms (NPS) are also important predictors in community-dwelling and institutionalized people with LOD, especially in proxy-reported QOL [19, 31, 36-38].…”
Section: Introductionmentioning
confidence: 99%
“…The association between increased depressive symptoms and reduced QOL is well established in LOD, as most studies show this to be a significant factor across dementia severity and type of residency [28-35]. Neuropsychiatric symptoms (NPS) are also important predictors in community-dwelling and institutionalized people with LOD, especially in proxy-reported QOL [19, 31, 36-38].…”
Section: Introductionmentioning
confidence: 99%
“…However, in this study there was no significant effect of the DAISY intervention on any quality of life measure. Based on results in a previous report29 we found that proxy rated quality of life probably better reflects progression of clinical measures as compared to patient-rated measures, and that EQ-5D is a suitable alternative to disease-specific quality of life measures in research. Additionally, it was assumed that the average trend between the observation points was linear.…”
Section: Discussionmentioning
confidence: 80%
“…However, we found that the majority of the QOL research has been conducted among caregivers rather than people suffering from AD themselves. On the other hand, previous longitudinal studies monitoring self-rated QOL in AD patients in the early stages (mild to moderate stages) have demonstrated not only better reliability and validity but also not much inter-rater differences compared to caregiver-rated QOL [53][54][55][56][57][58][59][60][61][62][63]. As a result, further research about the reliability and validity of QOL assessment for individuals with AD is required.…”
Section: Discussionmentioning
confidence: 99%